2001
DOI: 10.1097/00002030-200108004-00006
|View full text |Cite
|
Sign up to set email alerts
|

Why do young women have a much higher prevalence of HIV than young men? A study in Kisumu, Kenya and Ndola, Zambia

Abstract: Behavioural factors could not fully explain the discrepancy in HIV prevalence between men and women. Despite the tendency for women to have older partners, young men were at least as likely to encounter an HIV-infected partner as young women. It is likely that the greater susceptibility of women to HIV infection is an important factor both in explaining the male-female discrepancy in HIV prevalence and in driving the epidemic. Herpes simplex virus type 2 infection, which is more prevalent in young women than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
271
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(309 citation statements)
references
References 16 publications
31
271
3
1
Order By: Relevance
“…Relationships with longer-term partners are generally distinguish by emotional attachment and trust, which, in turn, have been linked to low levels of condom use in other studies (Harrison, Xaba, and Kunene 2002). In addition, wealthier men might engage in partnerships characterized by small age differences between partners, which are associated with higher levels of condom use and lower levels of HIV infection (Luke 2003, Kelly et al 2003, Gregson et al 2002, Glynn et al 2001.…”
Section: Analytical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships with longer-term partners are generally distinguish by emotional attachment and trust, which, in turn, have been linked to low levels of condom use in other studies (Harrison, Xaba, and Kunene 2002). In addition, wealthier men might engage in partnerships characterized by small age differences between partners, which are associated with higher levels of condom use and lower levels of HIV infection (Luke 2003, Kelly et al 2003, Gregson et al 2002, Glynn et al 2001.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…We also experimented with alternative forms of the continuous dependent variables to test for threshold effects. For example, several studies have found that large age differences of 10 or more years between sexual partners are associated with HIV infection and unsafe sexual behavior (Luke 2005a, Kelly et al 2003, Gregson et al 2002, Glynn et al 2001. We regress male characteristics on a dummy variable indicating an age difference between partners of 10 or more years versus less than 10 years; however, the coefficients on income and inherited land were small and imprecisely estimated.…”
mentioning
confidence: 99%
“…Young women (15–24 years) are at greater risk of being infected with HIV compared to their male counterparts. Although the prevalence of HIV and AIDS significantly dropped from 1.9% in 2013 to 1.6% in 2014 in Ghana [5], the proportion of infected women is higher than that of men, with cases among young women accounting for more than half of the prevalence in young people [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have underlined that self-reported variables regarding private information like sexual behavior are not truthfully reported 7 (Gersovitz et al, 1998;Glynn et al, 2001). …”
Section: Hiv and Risky Behaviormentioning
confidence: 99%